Europeanisation of the labor policy design in Georgia: mechanisms of change - Shubitidze,Sopiko (2024)
In this thesis, I explore the labor policy design change in the framework of the EU integration process in Georgia. The thesis aims to understand the incentives for recent changes in the labor policy domain covering the years 2014 and 2024, in particular, whether changes were a product of external incentives stemming from EU integration goals or it was the result of internal political will aiming to solve domestic problems in Georgia. This case study research utilizes a Europeanisation conceptual framework, and methodologically, it is based on interviewing methods and document analysis; all this has enabled an understanding of the major drivers for changes. I specifically focus on the Association Agreement between Georgia and the EU, which largely has influenced the current design of the labor policy in Georgia. Labor policy in Georgia had been in dire condition for several years, and significant changes took place when Georgia started preparatory work and later signed an Association Agreement with the EU in 2014. Georgia was granted candidateship status of the European Union in 2023, which has required advanced preparation for new necessary changes in all directions.
Keywords: Keywords: Europeanisation; Labor policy; Georgia; Social Policy; EU integration.